2017
DOI: 10.4236/psych.2017.813144
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies of Patterning

Abstract: Young children have been taught simple sequences of alternating shapes and colors, referred to as "patterning", for the past half century in the hope that their understanding of prealgebra and their mathematics achievement would be improved. The evidence that such patterning instruction actually improves children's academic achievement is scanty. However, recent research shows that instruction on more complex patterns produces advances in both mathematics and reading achievement. Patterning instruction should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The empirical research published previously (c.f. reviews by Burgoyne et al, 2017;Pasnak, 2017) has consistently shown relations between the patterning and mathematics scores of both preschoolers and first graders on a variety of mathematics measures, whether the patterns were simple alternations or complex like those used in the present research. However, this experiment and that of Shriver et al (2017) are the only ones conducted with kindergartners, and neither shows such a relationship.…”
Section: Discussionsupporting
confidence: 50%
“…The empirical research published previously (c.f. reviews by Burgoyne et al, 2017;Pasnak, 2017) has consistently shown relations between the patterning and mathematics scores of both preschoolers and first graders on a variety of mathematics measures, whether the patterns were simple alternations or complex like those used in the present research. However, this experiment and that of Shriver et al (2017) are the only ones conducted with kindergartners, and neither shows such a relationship.…”
Section: Discussionsupporting
confidence: 50%
“…The question remains whether the association with numerical ability is different for distinct pattern types. Some researchers have recently argued that the empirical evidence for a contribution to mathematical development is stronger for complex patterns, such as growing patterns, than for simple patterns, such as repeating patterns (Burgoyne, Witteveen, Tolan, Malone, & Hulme, 2017; Pasnak, 2017). So far, the association between patterning and numerical ability has been explained by the many regularities that can be found in both patterns and numbers.…”
Section: Patterning Numerical Ability and Their Associationmentioning
confidence: 99%
“…Such intervention studies could provide evidence for possible causal associations between SFOP, patterning ability and mathematical ability. Clearly, the number of intervention studies aimed at the design, implementation, and evaluation of innovating learning environments that pay intensive and systematic attention to the development of young children's patterning ability is increasing drastically (Pasnak, 2018), but, to the best of our knowledge, in these studies the role of the tendency to attend to mathematical patterns and structures is hardly addressed in the intervention and/or assessment part of these intervention studies.…”
Section: Sfopmentioning
confidence: 99%